Drought Conditions Enhance Groundwater Table Fluctuations Caused by Hydropower Plant Management. Issue 10 (10th October 2022) - Basilio Hazas, M.; Marcolini, G.; Castagna, M.; Galli, M.; Singh, T.; Wohlmuth, B.; Chiogna, G.
Abstract: Management of hydropower plants strongly influences streamflow dynamics and hence the interaction between surface water and groundwater. As dam operations cause variations in river stages, these can result in changes in the groundwater level at multiple temporal scales. In this work, we study the case of an Alpine aquifer, where weekly fluctuations are particularly pronounced. We consider an area with four river reaches differently impacted by reservoir operations and investigate the influence of these rivers on the common aquifer. Using continuous wavelet transform and wavelet coherence analysis, we show that weekly fluctuations in the groundwater table are particularly pronounced in dry years, in particular in the winter season, although the area of the aquifer impacted by dam operations remains almost unchanged. We thus observe that in Alpine catchments, surface water‐groundwater interaction is sensitive to the conditions determined by a specific hydrological year. We also investigate the influences of the river‐aquifer water fluxes and show that under dry conditions hydropeaking mainly affects their temporal dynamics. Our observations have significant consequences for predicting nutrient and temperature dynamics/regimes in river‐aquifer systems impacted by hydropower plant management. Plain Language Summary: The operation of hydropower plants affects the water level in the downstream part of the river, which in turn can alter the groundwater level. In this work, we study an Alpine aquifer crossed by rivers differently impacted by hydropower production. We use statistical tools to analyze the interaction between the rivers and the groundwater, and observe that this interaction is sensitive to the conditions of the hydrological year, such as dry periods. Key Points: Wavelet power spectrum and coherence analysis is used to study river‐aquifer interactions under dam operations in an Alpine catchment The impact of reservoir operations on the aquifer is strongest under low flow conditions but the area impacted shows little variation Under low flow conditions, dam operations considerably influence the frequency of the water exchange between rivers and aquifer